2018
DOI: 10.3390/ma11122561
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Treatments on the Degradation of Biomedical Mg Alloys—A Review Paper

Abstract: This report reviews the effects of chemical, physical, and mechanical surface treatments on the degradation behavior of Mg alloys via their influence on the roughness and surface morphology. Many studies have been focused on technically-used AZ alloys and a few investigations regarding the surface treatment of biodegradable and Al-free Mg alloys, especially under physiological conditions. These treatments tailor the surface roughness, homogenize the morphology, and decrease the degradation rate of the alloys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 120 publications
(302 reference statements)
0
29
0
Order By: Relevance
“… 50 In other cases, the corrosion resistance provided by the MgO layers on Mg strongly depended on the combination of surface morphology, surface roughness, surface area, surface wettability, and thickness of MgO. 64 , 65 Our previous results showed that MgO layers prepared by both anodization and EPD affected the degradation mode and rate of Mg after a 9-day immersion in the revised simulated body fluid (r-SBF) and Dulbecco’s modified Eagle’s medium (DMEM); that is, such oxide layers resulted in more homogeneous degradation mode and reduced the initial H 2 gas release when compared with noncoated Mg controls. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“… 50 In other cases, the corrosion resistance provided by the MgO layers on Mg strongly depended on the combination of surface morphology, surface roughness, surface area, surface wettability, and thickness of MgO. 64 , 65 Our previous results showed that MgO layers prepared by both anodization and EPD affected the degradation mode and rate of Mg after a 9-day immersion in the revised simulated body fluid (r-SBF) and Dulbecco’s modified Eagle’s medium (DMEM); that is, such oxide layers resulted in more homogeneous degradation mode and reduced the initial H 2 gas release when compared with noncoated Mg controls. 41 , 42 …”
Section: Discussionmentioning
confidence: 99%
“…Higher roughness is attributed to pit formation, resulting in higher difference between peaks and valleys. The roughness of a surface may have influence of the initial degradation of an implant or improve cell density or is even useful to vary the morphology of coatings [64][65][66][67]. For this reason, a variation of etching parameter allows the formation of a required morphology, dependent on the application.…”
Section: Discussionmentioning
confidence: 99%
“…This result was not in agreement with the roughness measurements, where the RMS and R a values of this film were higher than the 52.5 nm-thick TiO 2 film. Gawlik et al [1] stated that in some cases, the roughness does not influence the degradation rate of coated alloys [11]. The polarization resistance of the MgCa2Zn1Gd3 alloy with a thinner TiO 2 film was 445 Ω•cm 2 , while the thicker film reached an R p value of 479 Ω•cm 2 .…”
Section: X For Peer Review 7 Of 14mentioning
confidence: 99%
“…Magnesium alloys are widely used in medicine because of their many suitable properties, e.g., high mechanical strength, lightweight, etc. [1]. They are also nontoxic and biocompatible, but magnesium is one of the most electrochemically active metals [2].…”
Section: Introductionmentioning
confidence: 99%